The others of the Other: the space of alterity in Octavio Paz’s, Emmanuel Lévinas’s and Jean-Paul Sartre’s thoughts - Guimarães, Rodrigo (Revista de Letras, 2013)
This paper attempts to analyze the concepts of otredad [otherness] as defined by Octavio Paz, l’Autre et l’absolument Autre [the other and the absolute other], by Emmanuel Lévinas and l’être en-soi, l’être pour-soi et l’être pour-autrui [being-in-itself, being-for-itself and being-for others], by Jean-Paul Sartre in contemporary literature. The following books were analyzed: Paz’s El arco y la lira [The bow and the lyre] and La otra voz [The other voice]; Lévinas’s Autrement qu’être ou au-delà de l’essence [Otherwise than being: or beyond essence] and Sartre’s L’être et le néant [Being and nothingness], in which the processes of surpassing the cognoscent subject by the Other (in different modes of action) are more intensely shown.